2008
DOI: 10.1007/s11077-008-9057-z
|View full text |Cite
|
Sign up to set email alerts
|

Guest workers or unauthorized immigrants? The case of forest workers in the United States

Abstract: Forest management workers, H-2B guest workers, Undocumented workers, Legal status, Labor conditions, Latinos, Southeast, Pacific Northwest, Alabama, Oregon,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
2
16
0
1
Order By: Relevance
“…They also expressed a belief that supervisors have no compunction about firing them because they “know there are lots of other guest workers who are available to take your place if they want to fire you” (Focus Group Participant, quoted in Bush et al 2014, p. 795). This finding is consistent with other studies that have documented the atmosphere of fear under which undocumented and H-2B workers live while in the United States (Knudson and Amezcua 2005, Salazar et al 2005, Sarathy and Casanova 2008, Sarathy 2012, Holmes 2013). …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…They also expressed a belief that supervisors have no compunction about firing them because they “know there are lots of other guest workers who are available to take your place if they want to fire you” (Focus Group Participant, quoted in Bush et al 2014, p. 795). This finding is consistent with other studies that have documented the atmosphere of fear under which undocumented and H-2B workers live while in the United States (Knudson and Amezcua 2005, Salazar et al 2005, Sarathy and Casanova 2008, Sarathy 2012, Holmes 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Immigration policies and enforcement practices that contribute to creating a labor system with these inherent vulnerabilities and power imbalances need to be further examined and changed. Although our results are limited to the sample of workers who responded to our survey, the fact that other studies have found similar problems in forestry services and other labor-intensive industries that rely on immigrant and foreign labor supports our findings (Krissman 2000, Casanova and McDaniel 2005, Salazar et al 2005, Champlin and Hake 2006, Sarathy and Casanova 2008, Sarathy 2012, Sandoval 2013). …”
Section: Conclusion and Need For Further Researchsupporting
confidence: 86%
See 2 more Smart Citations
“…While recent scholarship tends to emphasize 'New West' economic migration, a small number of scholars continue to document the experiences of Latina/o migrants working in traditional Western industries. For example, Latina/o workers in Oregon's timber industry have received some attention (Sarathy andCasanova 2008, Wilmsen et al 2015), as have agricultural workers in Oregon's Willamette Valley (Nelson 2007, Stephen 2007. In Central Wyoming, Quechua migrants from the Peruvian Highlands have worked as sheepherders since the 1970s and continue to do so (Krögel 2010).…”
Section: Latina/o Migration In the Us Westmentioning
confidence: 99%